Cardiovascular evaluation of female rats with 6-OHDA-induced parkinsonism: Possible protection by ovarian hormones and participation of nitric oxide - Campos, Blenda Hyedra de; Jager, Lorena de; Reginato, Gabriela Souza; Santo Pereira, Rito; Crestani, Carlos Cesar [UNESP]; Pinge-Filho, Phileno; Martins-Pinge, Marli Cardoso (Elsevier B.V., 2020)
Aims: Parkinson's disease (PD) is a neurological disorder caused by environmental and genetic factors, char-acterized by the death of dopaminergic neurons of the substantia nigra pars compacta (SNpc), leading to a decrease of dopamine in the striatum. In addition to motor symptoms, PD has several abnormalities, among which are cardiovascular changes, such as orthostatic and postprandial hypotension, and blood pressure lability. Studies demonstrate gender differences in PD pathogenesis, indicating that female hormones have a protective role against disease development. However, no studies examining cardiovascular changes in a female rat model of parkinsonism exist. Main methods: Wistar female rats were subjected to ovariectomy (OVX) or sham surgery. After seven days, these animals were subjected to bilateral infusion of 6-hydroxydopamine (6-OHDA) or vehicle solution in their SNpc. On the 14th experimental day, a femoral artery catheterization was performed to record cardiovascular parameters after 24 h in conscious state. Analyses of cardiovascular variability and spontaneous baroreflex were performed. The nitrite (NO) concentration in the heart, thoracic aorta, abdominal aorta, and plasma was measured. Key findings: The sham-6-OHDA group had no decrease in the mean arterial pressure compared to sham-saline group, whereas the OVX-6-OHDA group presented a baseline decrease in comparison to sham-6-OHDA. The OVX-6-OHDA group showed an NO increase in the heart and abdominal aorta, whereas the sham-6-OHDA group did not. The very low frequency variability component decreased in the sham-6-OHDA but not in the OVX-6OHDA group. Significance: We suggest a cardiovascular protection by ovarian hormones in PD with a possible NO involvement.
Keywords: Arterial pressure; Heart rate; Autonomic; Parkinson's disease; Gender